ANALYSIS OF MICRO SMALL MEDIUM ENTERPRISE (MSME) DEVELOPMENT STRATEGIES IN LENTU VILLAGE, BONTORAMBA DISTRICT, JENEPONTO REGENCY(A Study on "Bu Tina" Onion Crackers Business) - Reski H.; Agus Syam; Muhammad Jufri; Muhammad Rakib; Sumiati Tahir (BORJUIS: JURNAL OF ECONOMY, 2025)
This study aims to analyze the development strategies of Micro, Small, and Medium Enterprises (MSMEs) with a case study on the "Bu Tina" onion crackers business in Lentu Village, Bontoramba District, Jeneponto Regency. The research uses a qualitative descriptive method by collecting data through interviews, observations, and documentation. SWOT analysis is employed to identify internal and external factors that influence business development. The results show that "Bu Tina" onion crackers business has strengths in product uniqueness and local raw materials, but faces challenges in limited marketing reach and production capacity. Opportunities such as increasing consumer demand and support from local government programs can be leveraged to overcome these weaknesses. The recommended strategy is a growth-oriented approach through product diversification, strengthening branding, and expanding distribution channels. The study highlights the importance of strategic planning in improving MSME sustainability and competitiveness at the village level.